2015
DOI: 10.1245/s10434-015-4909-1
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 Expression Status is Prognostic in Patients with Advanced Thoracic Esophageal Squamous Cell Carcinoma

Abstract: High CXCL10 expression is an independent prognostic factor and has the potential to serve as a clinically useful marker of the need for adjuvant chemotherapy after surgery in patients with advanced thoracic ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In addition, an increased number of CD14 + HLA-DR low / -monocytes was demonstrated to be an independent prognostic factor in patients with non-small lung cancer (13). The present study revealed that the number of CD14 + HLA-DR low / -monocytes was associated with CXCL10 and CCL2 expression, and in a previous study a high CXCL10 expression in cancer tissues was demonstrated to be associated with a favorable survival rate in patients with esophageal cancer (14). Therefore, it may be of interest to investigate whether the serum concentration of CXCL10 or CCL2 is a useful prognostic marker for patients with cancer.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, an increased number of CD14 + HLA-DR low / -monocytes was demonstrated to be an independent prognostic factor in patients with non-small lung cancer (13). The present study revealed that the number of CD14 + HLA-DR low / -monocytes was associated with CXCL10 and CCL2 expression, and in a previous study a high CXCL10 expression in cancer tissues was demonstrated to be associated with a favorable survival rate in patients with esophageal cancer (14). Therefore, it may be of interest to investigate whether the serum concentration of CXCL10 or CCL2 is a useful prognostic marker for patients with cancer.…”
Section: Discussionsupporting
confidence: 70%
“…albumin and hemoglobin) between the two groups. Genetic factors may also contribute to the different individual responses to NAT (25)(26)(27). At present, however, there is no clear explanation and further study will be required to resolve this issue.…”
Section: Figure 3 Overall Survival Stratified According To Psoas Musmentioning
confidence: 96%
“…The reduction of not only CXCR3, but also of CXCL9 and CXCL10 could suppress cancer metastatic frequencies in melanoma,[55] colon cancer,[7, 52, 56] and breast cancer models[57, 58]. There is a consensus among some groups about the association between CXCL9 [59, 60] and CXCL10 [54, 61] expression and poor prognosis or negative response to existing therapy, whereas others report that CXCL9 [6264] and CXCL10 [65, 66] are related to opposite results. These differences in reports may be due to complex relationship between each ligand depending on the cancer types.…”
Section: Cxcl9 Cxcl10 Cxcl11/cxcr3 Axis For Immune Responsementioning
confidence: 99%